Coaxial carbon@boron nitride nanotube arrays with enhanced thermal stability and compressive mechanical properties - Teo, Edwin Hang Tong (2017)
Vertically aligned carbon nanotube (CNT) arrays have aroused considerable interest because of their remarkable mechanical properties. However, the mechanical behaviour of as-synthesized CNT arrays could vary drastically at a macro-scale depending on their morphologies, dimensions and array density, which are determined by the synthesis method. Here, we demonstrate a coaxial carbon@boron nitride nanotube (C@BNNT) array with enhanced compressive strength and shape recoverability. CNT arrays are grown using a commercially available thermal chemical vapor deposition (TCVD) technique and an outer BNNT with a wall thickness up to 1.37 nm is introduced by a post-growth TCVD treatment. Importantly, compared to the as-grown CNT arrays which deform almost plastically upon compression, the coaxial C@BNNT arrays exhibit an impressive ∼4-fold increase in compressive strength with nearly full recovery after the first compression cycle at a 50% strain (76% recovery maintained after 10 cycles), as well as a significantly high and persistent energy dissipation ratio (∼60% at a 50% strain after 100 cycles), attributed to the synergistic effect between the CNT and outer BNNT. Additionally, the as-prepared C@BNNT arrays show an improved structural stability in air at elevated temperatures, attributing to the outstanding thermal stability of the outer BNNT. This work provides new insights into tailoring the mechanical and thermal behaviours of arbitrary CNT arrays which enables a broader range of applications.